2021
DOI: 10.1161/jaha.120.018548
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of New‐Onset Postoperative Atrial Fibrillation after Noncardiac Surgery

Abstract: Background Postoperative atrial fibrillation (POAF) is common after cardiac surgery, but little is known about its incidence and natural course after noncardiac surgery. We evaluated the natural course and clinical impact of POAF and the long‐term impact of anticoagulation therapy in patients without a history of atrial fibrillation (AF) undergoing noncardiac surgery. Methods and Results We retrospectively analyzed the database of Asan Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The epidemiology of AFNOAI in our study is consistent with previous data, lending credence to the generalizability of our results. AFNOAI was rare in our study (1.8%), but the AFNOAI persistence rate was high (38%), similar to prior research [ 1 , 3 , 7 ]. Half of patients with AFNOAI expired in hospital, and over half of hospital survivors died in the 5 years after discharge, again consistent with existing evidence of a high mortality rate in this cohort [ 7 - 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The epidemiology of AFNOAI in our study is consistent with previous data, lending credence to the generalizability of our results. AFNOAI was rare in our study (1.8%), but the AFNOAI persistence rate was high (38%), similar to prior research [ 1 , 3 , 7 ]. Half of patients with AFNOAI expired in hospital, and over half of hospital survivors died in the 5 years after discharge, again consistent with existing evidence of a high mortality rate in this cohort [ 7 - 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…The importance of cardiac factors demonstrated in our study reinforces prior data in patients who had undergone non-cardiac surgery, which showed that hypertension and left atrial enlargement were associated with persistence of new onset AF [ 3 ]. The association with age likely mirrors the increasing prevalence of AF in the older population [ 4 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…655,656 Although many post-operative AF episodes are self-terminating and some are asymptomatic, post-operative AF has been associated with a four-to five-fold risk of AF recurrence in the 5 years following cardiac surgery, while the risk of recurrence after NCS is less well described. [656][657][658][659][660] Importantly, post-operative AF is a risk factor for stroke, MI, and death compared with non-post-operative AF patients. 656,658,661 Post-operative AF may also lead to haemodynamic instability, prolonged hospital stay, infections, renal complications, bleeding, increased in-hospital death, and greater healthcare costs.…”
Section: Atrial Fibrillation and Other Relevant Arrhythmiasmentioning
confidence: 99%
“…Previous epidemiological investigations have revealed that AF is frequently associated with various structural heart diseases and systemic comorbidities and other miscellaneous predisposing factors, encompassing congenital heart disease, coronary heart disease, rheumatic heart disease, cardiomyopathy, cardiac and noncardiac surgery, essential hypertension, hyperthyroidism, diabetes, chronic obstructive pulmonary disease, chronic kidney disease, inflammation, obstructive sleep apnea, imbalanced serum electrolytes, obesity, and unhealthy lifestyle. 1 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 However, in up to 30% of AF cases, AF occurs in the absence of the above‐mentioned, well‐recognized cardiac conditions or modifiable risk precipitants (termed as idiopathic AF). 2 Recently, increasing studies have demonstrated substantial familial clustering of AF, with the heritability of AF being as high as 62%, which highlights a strong genetic component underlying AF.…”
mentioning
confidence: 99%